(3dWGja Gdeff aj efGbH GdTjN CHj GdYHGS hTjNI CHj GdMSfs - (3CMeO Hf eMeO Hf YHO GdcQje Hf YWGA Gddg GdScfOQj, GHf YWGA Gddg , JGL GdOjf CHh GdaVd,J (B709 (3g` s ((3GdCScfOQjI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi aJM dChdjGFg HGH eMHJg CeG HYO aEfi bUOJ ai gPG GdcJGH Cf CPcQ LedkG ef aVGFd SjOfG TgGH GdOjf CHj GdYHGS CMeO Hf YeQ GdCfUGQi GdeQSi s
(3BNQgG (B:s
(3Ydi GdESdGe aGbVHfi SdjekG ef GdCaGJ eeMh GdPfhH cPdc cd ef hGdjJ ajce hhGdGfi HCLRd GdfUjH Je cJGH dWGja GdeJf HMeO Gddg hYhfg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B121s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1554s
Keywords: (3GdJUha hGdBOGH GdTQYjIs